As mudanças de linha editorial na Folha de São Paulo (1979-1989) - Muniz, Altemar da Costa (1999)
This job tries to explain the changes of opinion of the Folha de São Paulo newspaper in the period of 1979 to 1989 about economical development in the state when showing its publishing line in the political developmental national defense established in 1968 for the support of orientations neoliberal of regulamentations and limitations of state intervention. Based on research in its publishing allied to articles of Folha de São Paulo rebuilt its process of adhesion to the distating ideas of the 1980 decade, relating it with the political and financial changes that the country has been through. We have tried to dismitify its self representations of the newspaper that justified the reorientation of the publishing line as a result of non dogmatical character, flexible, and aware to the worldwide changes of the newspaper, by the analysis of these discursive constructions showed in the publishing, confronted them whit the business and political information of its owners, gotten by interview, accounts of journalists that worked and still work at Folha de São Paulo newspaper, in its financial balances and is studies about the paulista diary in its financial political journalistical aspects. The presenting lecture inserts itself in the process of introduction of comprehension of neoliberal hegemony in the press and in the Brazilian society that has a relatively short space that inhibited and put in its defense of nationalist tendencies shown in the ideal of the academical business elites and politics of the country.